2013
DOI: 10.1590/0037-8682-0198-2013
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and nutritional evaluation of patients with visceral leishmaniasis before and after treatment with leishmanicidal drugs

Abstract: Revista da Sociedade Brasileira de Medicina Tropical 46(6):735-740, Nov-Dec, 2013http://dx.doi.org/10.1590/0037-8682-0198-2013 ABSTRACT Introduction: Visceral leishmaniasis (VL) is caused by the intracellular protozoan Leishmania donovani complex. VL may be asymptomatic or progressive and is characterized by fever, anemia, weight loss and the enlargement of the spleen and liver. The nutritional status of the patients with VL is a major determinant of the progression, severity and mortality of the disease, as i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 46 publications
(60 reference statements)
4
12
0
Order By: Relevance
“…6 Leishmania donovani causes lipid profile changes and affects the kidney which leads to alteration of glomerular and tubular functions. 4,9 In the present study, the mean of serum ALT, AST, and ALP was significantly higher in VL patients than healthy controls. This finding was in line with the previous study conducted in Sudan, Iraq, and India 6,8,12,13 which was reported a significantly higher value of AST, ALT, and ALP in VL patients.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…6 Leishmania donovani causes lipid profile changes and affects the kidney which leads to alteration of glomerular and tubular functions. 4,9 In the present study, the mean of serum ALT, AST, and ALP was significantly higher in VL patients than healthy controls. This finding was in line with the previous study conducted in Sudan, Iraq, and India 6,8,12,13 which was reported a significantly higher value of AST, ALT, and ALP in VL patients.…”
Section: Discussionsupporting
confidence: 45%
“…7 Visceral leishmaniasis patients presented with enlarged liver and shows higher value of ALT, AST, ALP, 8 and the disease is also characterized by severe hypertriglyceridemia with reduced levels of total cholesterol, LDL-cholesterol, and HDL-cholesterol in adult patients. 9 Visceral leishmaniasis also affects the kidney and kidney involvement in chronic leishmaniasis is frequently associated with increased morbidity and mortality. Acute kidney injury was found in a significant proportion of VL patients.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly to the results obtained by Gatto et al . 23 , here we showed that serum albumin is slightly reduced during VL and the treatment of children, whether using amphotericin B or glucantime alone or in combination with Zn supplementation, increases serum albumin to normal levels ( Figure 1D ).…”
Section: Resultsmentioning
confidence: 58%
“…We believe that this finding is a proxy measure for malnourishment. It is worth noting that a previous study from our group, which included body measures, bioimpedance and biochemical assessment, found relevant evidence of malnourishment in VL patients, as compared to healthy controls (Gatto et al, 2013). Even though those measures could not be retrospectively assessed in the present analysis, it is tempting to infer that the worse the nutritional indicators, the greater the likelihood of relapse.…”
Section: Discussionmentioning
confidence: 73%